Clonal hematopoiesis and risk of prostate cancer in large samples of European ancestry men. Issue 3 (26th August 2022) - Wang, Anqi; Xu, Yili; Yu, Yao; Nead, Kevin T; Kim, TaeBeom; Xu, Keren; Dadaev, Tokhir; Saunders, Ed; Sheng, Xin; Wan, Peggy; Pooler, Loreall; Xia, Lucy Y; et al.
Abstract: Little is known regarding the potential relationship between clonal hematopoiesis (CH) of indeterminate potential (CHIP), which is the expansion of hematopoietic stem cells with somatic mutations, and risk of prostate cancer, the fifth leading cause of cancer death of men worldwide. We evaluated the association of age-related CHIP with overall and aggressive prostate cancer risk in two large whole-exome sequencing studies of 75 047 European ancestry men, including 7663 prostate cancer cases, 2770 of which had aggressive disease, and 3266 men carrying CHIP variants. We found that CHIP, defined by over 50 CHIP genes individually and in aggregate, was not significantly associated with overall (aggregate HR = 0.93, 95% CI = 0.76–1.13, P = 0.46) or aggressive (aggregate OR = 1.14, 95% CI = 0.92–1.41, P = 0.22) prostate cancer risk. CHIP was weakly associated with genetic risk of overall prostate cancer, measured using a polygenic risk score (OR = 1.05 per unit increase, 95% CI = 1.01–1.10, P = 0.01). CHIP was not significantly associated with carrying pathogenic/likely pathogenic/deleterious variants in DNA repair genes, which have previously been found to be associated with aggressive prostate cancer. While findings from this study suggest that CHIP is likely not a risk factor for prostate cancer, it will be important to investigate other types of CH in association with prostate cancer risk.